Analyzing the needs of appropriate counseling techniques and personality of problematic students in technical training institute: A qualitative study - Yusof, Norizan; Abdul Aziz, Abdul Rashid; Abdul Wahab, Muhammad Nubli (Universiti Malaysia Pahang, 2022)
The transition from formal education to technical and vocational education has an impact on student adaptation. Technical and Vocational Education is one of the educational alternatives for students who have a tendency to be interested in technical streams. Human capital through technical and vocational education is able to develop a superior and balanced personality through knowledge, skills, abilities and expertise. Technical stream students are faced with various transitions, especially the school system that changes when they enter the technical field. Therefore, adaptation to the transition of learning levels needs to be done by students to ensure that students at the Technical Training Institute are able to adapt to the changes they are going through. The process of adapting to these changes requires the help of counselors who are skilled with various techniques that suit the personality of the students at the Technical Training Institute. Counseling techniques based on the theory of thought alone are not suitable for technical students. Therefore, it is necessary to analyze the needs to see the reaction, behavior and the need for appropriate counseling techniques based on the student's personality. This study is a qualitative study to see the personality of students at the Technical Training Institute (ILT). This study is a needs study carried out qualitatively to see the appropriate techniques in the application of counseling to technical stream students. This study was conducted using a qualitative methodology. Several data collection methods are used such as interview techniques, document analysis and observation. The selection of several data collection methods is to meet the validity of the study, which is data triangulation. This study was conducted at five technical training institutes around Kuantan. This study uses a non-probability sampling technique and uses the snowball method to obtain study participants who meet the researcher's criteria. The results of the study found that the theme of problematic students is divided into three, namely the personality of problematic students, the main problems of students and the appropriate counseling technique approach for students at the Technical Training Institute.